Real-world outcomes with ibrutinib in relapsed or refractory mantle cell lymphoma : a Danish population-based study - Trab, Trine; Chanchiri, Iman; Al-Mashhadi, Ahmed Ludvigsen; Dall, Emma Berggren; Rasch, Stine; Johansen, Mette; Husby, Simon; Simonsen, Mikkel Runason; Clausen, Michael Roost; Larsen, Thomas Stauffer; Christensen, Jacob Haaber; Pedersen, Robert Schou; et al. (Blood Neoplasia, 2025)
Ibrutinib was approved for relapsed/refractory (R/R) mantle cell lymphoma (MCL) based on high response rates in clinical trials, but it is unclear how effective ibrutinib is in the real-world setting. This study provides population-based response rates and survival estimates and characterization of prognostic indicators and adverse events (AEs) to ibrutinib for patients with R/R MCL. All patients diagnosed with MCL in Denmark from 2010 to 2022 were identified in the Danish Lymphoma Registry and screened for eligibility. Data were collected from health records. Patients receiving ibrutinib in second or later lines were included and followed from ibrutinib start until death or last follow-up. End points were overall response rate (ORR), progression-free survival (PFS), overall survival (OS), frequency of AEs, and AE-related discontinuation and dose reductions. In total, 146 patients were included (median age, 73 years); 90 (62%) received ibrutinib in second line. ORR was 56%, median PFS 5.8 months, and median OS 12.0 months. In Cox regressions, factors associated with inferior PFS were Ki67 of ≥50% (hazard ratio [HR], 2.34; 95% confidence interval [CI], 1.47-3.71), blastoid or pleomorphic subtype (HR, 3.00; 95% CI, 2.04-4.41), early relapses (HR, 1.65; 95% CI, 1.15-2.36), and refractory disease (HR, 1.57; 95% CI, 1.07-2.30). Three-year cumulative incidences of discontinuation and dose reductions owing to AEs were 19% and 22%, respectively. Median OS after ibrutinib discontinuation was 1.9 months. In conclusion, real-world outcomes after initiation of ibrutinib for R/R MCL were poorer than observed in clinical trials, and dose-limiting toxicities were common, emphasizing the need for more effective treatments and dose-optimization studies.
Publisher Copyright: © 2025 The American Society of Hematology